Elevation of branched-chain amino acid levels in diabetes and NAFL and changes with antidiabetic drug treatment. Issue 3 (May 2015) - Iwasa, Motoh; Ishihara, Tomoaki; Mifuji-Moroka, Rumi; Fujita, Naoki; Kobayashi, Yoshinao; Hasegawa, Hiroshi; Iwata, Kazuko; Kaito, Masahiko; Takei, Yoshiyuki
Summary Diabetes mellitus (DM), non-alcoholic fatty liver (NAFL), and obesity are associated with elevated branched-chain amino acid (BCAA) levels, but the mechanism and significance of this has not been elucidated. Eighty-four subjects were enrolled including 43 with DM. Serum BCAA levels were positively correlated with waist–hip ratio and ALT. Serum BCAA levels in subjects with DM were higher than non-DM and those in subjects with NAFL were also higher than non-NAFL. Treatment with pioglitazone and alogliptin (19 of 43 DM subjects) improved serum haemoglobin A1c and decreased BCAA levels. The decrease in BCAAs with improved glucose metabolism suggests that abnormal glucose metabolism is also a factor in elevated BCAA levels.